2014
DOI: 10.3389/fnhum.2014.00485
|View full text |Cite|
|
Sign up to set email alerts
|

EEG beta suppression and low gamma modulation are different elements of human upright walking

Abstract: Cortical involvement during upright walking is not well-studied in humans. We analyzed non-invasive electroencephalographic (EEG) recordings from able-bodied volunteers who participated in a robot-assisted gait-training experiment. To enable functional neuroimaging during walking, we applied source modeling to high-density (120 channels) EEG recordings using individual anatomy reconstructed from structural magnetic resonance imaging scans. First, we analyzed amplitude differences between the conditions, walkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
186
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(229 citation statements)
references
References 49 publications
(74 reference statements)
41
186
2
Order By: Relevance
“…Some attempts to enhance the interpretability of brain oscillations are already ongoing (e.g. [90,91]).…”
Section: Signal Processing and Decodingmentioning
confidence: 99%
“…Some attempts to enhance the interpretability of brain oscillations are already ongoing (e.g. [90,91]).…”
Section: Signal Processing and Decodingmentioning
confidence: 99%
“…Our laboratory has recorded electrocortical spectral fluctuations during treadmill walking in healthy, young adults (Gwin et al, 2011; Sipp et al, 2013). Other groups have also proved the feasibility of measuring scalp electrocortical signals during human walking, at speeds ranging from 0.42 m/s to 1.9 m/s, to provide insight into brain function (Gramann et al, 2010; Cheron et al, 2012; Lau et al, 2012; Severens et al, 2012; Wagner et al, 2012; Seeber et al, 2014; Seeber et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The beta suppression may be related to initiation and execution of movement, while the prefrontal beta increase to cognitive top-down control. Seeber et al (2014) found that during active walking the upper mu (10–12 Hz) and beta (18–30 Hz) oscillations were suppressed compared to upright standing and the significant beta ERD activity was located focally in central sensorimotor areas. They also found that low gamma (24–40 Hz) amplitudes were modulated related to the gait phase.…”
Section: Introductionmentioning
confidence: 99%